Security and privacy for e-business - Ghosh, Anup K.
With billions of dollars at stake in e-commerce, companies are becoming much more concerned about security and privacy issues. Hackers have made headlines by breaking into Web sites that aggregate sensitive information about all of us, which has caused growing public concern about personal and financial privacy. Some online businesses are inadvertently "sharing" data with others when they interoperate systems. This book examines the external threats to a company's system and explains how to react if your system and business goals diverge. It also presents a nuts-and-bolts guide to enhancing security and safeguarding gateways. Readers will find an extensive reference section for the many tools, standards, and watchdog agencies that aid in the security/privacy effort